2014
DOI: 10.1016/j.leukres.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine plus alemtuzumab (FA) front-line treatment in young patients with chronic lymphocytic leukemia (CLL) and an adverse biologic profile

Abstract: a b s t r a c tIn 45, ≤60 years old patients with CLL and an adverse biologic profile, a front-line treatment with Fludarabine and Campath (Alemtuzumab ® ) was given. The overall response rate was 75.5%, the complete response rate (CR) 24.4% with the lowest CR rates, 16.7% and 8.3%, in 11q and 17p deleted cases. The 3-year progression-free survival (PFS) and overall survival were 42.5% and 79.9%, respectively. PFS was significantly influenced by CLL duration, beta2-microglobulin, and improved by post-remission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…TP53 encodes for the p53 protein, a transcription factor involved in essential cell functions, such as DNA repair, cell cycle control, apoptosis, aging, and stemness [ 1 , 2 ]. Aberrant p53 function, due to 17p deletion (del(17p)) and/or TP53 mutation, is associated with poor prognosis in chronic lymphocytic leukemia (CLL) patients [ 3 5 ]. Alterations of TP53 occur in about 10 % of untreated CLL patients [ 6 , 7 ], but up to 50 % in relapsed or refractory cases [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…TP53 encodes for the p53 protein, a transcription factor involved in essential cell functions, such as DNA repair, cell cycle control, apoptosis, aging, and stemness [ 1 , 2 ]. Aberrant p53 function, due to 17p deletion (del(17p)) and/or TP53 mutation, is associated with poor prognosis in chronic lymphocytic leukemia (CLL) patients [ 3 5 ]. Alterations of TP53 occur in about 10 % of untreated CLL patients [ 6 , 7 ], but up to 50 % in relapsed or refractory cases [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic lymphocytic leukemia (CLL) is a heterogeneous disease with highly variable clinical manifestations, ranging from asymptomatic at the time of diagnosis to a progressive symptomatic disease that is poorly responsive to the common immuno-chemotherapeutic regimens [12]. Genomic sequencing studies have revealed a number of recurrently mutated genes in CLL [35].…”
Section: Introductionmentioning
confidence: 99%
“…Alemtuzumab in combination with fludarabine achieved an ORR of 58·3% and a CR rate of 7·8% in patients with del(17p) younger than 60 years old. Absence of bulky lymphadenopathy, high β 2 ‐microglobulin levels and longer time interval from initial diagnosis were predictive of favourable PFS, which was similar to that in patients without the deletion: 51% vs. 60% survived after 3 years (Mauro et al , ). Another recent randomized trial showed that, while alemtuzumab combined with fludarabine and cyclophosphamide successfully prolonged PFS (but not OS) in patients with high risk cytogenetics, it failed to do so in the del(17p) subgroup (although the study was not adequately powered to conduct a complete subgroup analysis) (Geisler et al , ).…”
Section: Hitting Roadblocks: Inferior Chemotherapy Responses In Del(1mentioning
confidence: 72%